The Role and Current Status of IFRS in the Completion of National Accounting Rules – Evidence from Portugal. (4th May 2017) - Isidro, Helena; Pais, Cláudio
Abstract: We explain the process and documents that internalise the European Union (EU) Directive No. 2013/34 in Portugal. The Portuguese accounting standard setting body, the Comissão de Normalização Contabilística (CNC), is the entity in charge of the preparation and implementation of accounting standards. As such, CNC was responsible for the implementation of the EU Directive in Portugal. The Directive was approved by Decree-Law No. 98/2015 of 2 June 2015, but many important aspects of the Directive had already been adopted in Portugal when a new accounting system, designated Sistema de Normalização Contabilística (SNC), was introduced in 2009. Decree-Law No. 98/2015 of 2 June 2015 amends the SNC system to incorporate news aspects of the 2013 EU Directive. The current accounting rules in Portugal are strongly aligned with IFRS but some differences exist.